Analisis strategi pemasaran wahana rekreasi agro wisata Tirto Arum Baru Kendal ditengah pandemi covid-19 tahun 2020 - Fahmi Adil Pratama; Supriyono Supriyono (Journal of Physical Activity and Sports (JPAS), 2021)
Tirto Arum Baru Kendal Agro Tourism is one of those affected by Covid-19 pandemic. Due to that condition, the manager has to change the marketing strategy that has been carried out. The purpose is to analyze Tirto Arum Baru Kendal Agro-tourism marketing strategy employed in the midst of the Covid-19 pandemic using the 7P marketing mix (Product, Price, Promotion, Place, People, Process and Physical Evidence) and a SWOT analysis. This research used qualitative descriptive approach, analyzing managers, employee and visitors as research subjects. Data collection techniques using observation, interviews and documentation. The data validity technique used triangulation to compare the results of data collection. The data analysis technique uses data reduction and data presentation to draw conclusions. This research used qualitative descriptive approach, analyzing managers, employee and visitors as research subjects. Data collection techniques using observation, interviews and documentation. The data validity technique used triangulation to compare the results of data collection. The data analysis technique uses data reduction and data presentation to draw conclusions. The result of the research showed that the marketing strategy analysis carried out by the Tirto Arum Baru Kendal Agro Tourism is in accordance with the 7P marketing mix components. In addition, the implementation of health protocols carried out during the pandemic is used as an example by the Regional Government for other recreational facilities in Kendal Regency.